Biosynthesis of Chitosan and Chitosan AgNps of Penaeus monodon and their potential antimicrobial activity - G. Carolin Priya Stepin,; J. Shifa Vanmathi,; R. Jenifer, (The Bioscan, 2025)
The noval discovery of biopolymer with antibacterial properties gains importance, hence the present study deals with the synthesis of chitosan from biodegradable shell waste of Penaeus monodon through several process like demineralization, deproteinization and deacetylation. The Chitosan AgNps were synthesized and characterized by UV, FTIR and XRD. The Chitosan AgNps of Penaeus monodon were subjected to antibacterial activity against six bacterial strains namely, Bacillus subtilis , Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus mutans respectively. Among all tested bacteria, Escherichia coli showed maximum zone of inhibition at 300 μg/ml concentration and Klebsiella pneumonia showed minimum zone of inhibition at 300 μg/ml concentration.